Faktor Yang Berhubungan dengan Pengetahuan Ibu Hamil Tentang HIV Aids di Wilayah Kerja Puskesmas Kuok Kabupaten Kampar - Hastuty, Milda; Syahda, Syukrianti; Riani, Riani (Jurnal Ners, 2024)
AIDS is also a pandemic problem that is very worrying because in addition to this disease there is no vaccine and drug that can prevent the spread to others, this disease also has an asymptomatic phase (without symptoms) which is relatively long and long in the process of the disease so that its development is like an iceberg phenomenon. Based on data on the achievement of minimum service standards (MSS) in Riau Province from January to June 2022, 14.7 percent of achievements were recorded with 190,442 people. With the highest rank in Dumai City at 34.1 percent and the lowest occupied by Siak Regency with an achievement of 7.4 percent. The purpose of this study was to determine the factors associated with pregnant women’s knowledge about HIV AIDS at Kuok Health Center, Kampar Regency in 2023. This study used observational analytic quantitative research with a cross sectional design. The research was conducted in March - May 2023 in the Kuok Health Center Working Area, Kampar Regency. The population in this study were all pregnant women who came to the Kuok Health Center from January to March 2023 as many as 76 pregnant women. The sampling technique used in this study was total sampling. Based on the results of statistical tests with chi square, the p-value obtained for the mother’s education variable is 0.022 (p<0.05), for variable mass media information 0.000 (p<0.05), for variable information from health workers. Based on these results, it is expected that pregnant women increase their knowledge by reading various articles related to HIV AIDS and attending various counseling on HIV AIDS. Keywords: HIV AIDS Knowledge, Maternal Education, Mass Media Information, Health Worker Information